Demystifying Excess Immune Response in COVID-19 to Reposition an Orphan Drug for Down-Regulation of NF-κB: A Systematic Review - Apparao Peddapalli; Manish Gehani; Arunasree M. Kalle; Siva R. Peddapalli; Angela E. Peter; Shashwat Sharad (Viruses, 2021)
The immunological findings from autopsies, biopsies, and various studies in COVID-19 patients show that the major cause of morbidity and mortality in COVID-19 is excess immune response resulting in hyper-inflammation. With the objective to review various mechanisms of excess immune response in adult COVID-19 patients, Pubmed was searched for free full articles not related to therapeutics or co-morbid sub-groups, published in English until 27 October 2020, irrespective of type of article, country, or region. Joanna Briggs Institute’s design-specific checklists were used to assess the risk of bias. Out of 122 records screened for eligibility, 42 articles were included in the final review. The review found that eventually, most mechanisms result in cytokine excess and up-regulation of Nuclear Factor-κB (NF-κB) signaling as a common pathway of excess immune response. Molecules blocking NF-κB or targeting downstream effectors like Tumour Necrosis Factor α (TNFα) are either undergoing clinical trials or lack specificity and cause unwanted side effects. Neutralization of upstream histamine by histamine-conjugated normal human immunoglobulin has been demonstrated to inhibit the nuclear translocation of NF-κB, thereby preventing the release of pro-inflammatory cytokines Interleukin (IL) 1β, TNF-α, and IL-6 and IL-10 in a safer manner. The authors recommend repositioning it in COVID-19.